Students Experienced Sexual Violence and Obstacles in Handling It According to Regulation of the Minister of Education, Culture, Research and Technology Number 30 of 2021 Concerning Prevention and Handling of Sexual Violence in Higher Education - Widiastuti; Yokhebed Arumdika Prabawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Regulation of Education, Culture and Research and TechnologyMinister Number 30 2021 concerning the Prevention and Handling of Sexual Violence in Higher Education stipulates that one year after the enactment of this regulation, each university must form a Task Force. However, there are not a few universities that have not formed the Task Force, the reason is because in the colleges concerned there is no sexual violence. This paper aims to uncover the forms of sexual violence that occur, and examine The Regulation of Education, Culture and Research and Technology Minister Number 30 2021 in dealing with sexual violence on campus whose perpetrators come from members of the public society. This research is a normative legal research, and used deductive logic to analyze violent sexual that occur on campus. The results showed that sexual violence that occurred covered verbal, physical and electronic-based violence. Obstacles to handling sexual assault cases are because the campus has not established a task force for the prevention and handling of sexual violence. In addition, the Regulation of the Minister of Cultural Education, Research and Technology Number 30 of 2021 does not give authority for campuses to check and sanction perpetrators of sexual violence from the outsider, but the campus is only authorized to protect witnesses or victims who come from the outsider.